My feelings - Jenner, Caryn (London Franklin Watts, 2010)
Addresses the different aspects children have to understand as they take a larger and more active role in their communities - from exploring the different kinds of families they are part of to understanding feelings and how their behaviour affects others
Education
1
Keywords: Emotions -- Juvenile literature; Emotions